Private Higher Education: Patterns, Divergences, and Regional Trends - Levy, Dan (International Higher Education, 2025)
<h3 id="private-higher-education-phe-has-grown-enormously-and-become-quite-diversified-while-concentrated-in-asia-and-the-americas-phe-is-nearly-ubiquitous-globally-this-overview-identifies-broader-phe-patterns-and-the-chief-ways-that-regional-and-country-variation-bend-or-even-break-from-the-geographically-broad-patterns-striking-differences-persist-between-private-and-public-and-new-differences-arise-few-key-concerns-in-contemporary-higher-education-can-any-longer-be-contemplated-without-the-inclusion-of-phe" data-pm-slice="1 1 []">Private higher education (PHE) has grown enormously and become quite diversified. While concentrated in Asia and the Americas, PHE is nearly ubiquitous globally. This overview identifies broader PHE patterns and the chief ways that regional and country variation bend or even break from the geographically broad patterns. Striking differences persist between private and public, and new differences arise. Few key concerns in contemporary higher education can any longer be contemplated without the inclusion of PHE.